Goodbyes and returns: The doors in César Vallejo - García, Mara L. (Espergesia, 2018)
“Goodbyes and returns: The doors in César Vallejo”, focuses on the study of doors, recurring elements in the work of the author of Trilce. These have a presence in the life and poetry of the universal poet, César Vallejo. The doors, in Vallejo’s poetry, are entrances to the unknown and spaces related to the female. It is there where the woman thinks and dreams. The gates are metonymy of the home of childhood and innocence. In Vallejo, the doors are relevant and there are scarce studies on this symbol that appears insistently in his work. For the author of Human Poems, the door has a material but also a spiritual meaning. She not only plays the role of protecting physical housing, but has human characteristics; the door feels and suffers. The doorway experiences pain and anguish and is intimately connected with Vallejo’s lyric speaker. The doors in Vallejo have as their essence the memories of childhood and constitute an essential part of the mother’s house. The purpose of this essay is to plant the seed for future studies on the liminal spaces in Vallejo.